What are the Limits of Social Inclusion? Indigenous Peoples and Indigenous Governance in Canada and the United States. Issue 2 (3rd April 2019) - Cornell, Stephen; Jorgensen, Miriam
ABSTRACT: Contemporary debates about poverty and its mitigation often invoke the idea of social inclusion: the effort to increase the capacities and opportunities of disadvantaged populations to participate more fully in the economy, polity, and institutions of developed societies. While practical outcomes have been inconsistent, this idea has been prominent in the social policies of both Canada and the United States. Both generally see themselves as liberal democracies committed to building socially inclusive societies, and both have adopted policies in support of that goal. However, we argue in this article that social inclusion, as presently conceived, fails to comprehend or address the distinctive situation of Indigenous peoples in both of these countries. Our critique focuses on four aspects of social inclusion as applied to Indigenous peoples: the external conception of needs, the individualization of both problems and solutions, the favoring of distributional politics over positional politics, and the conditionality of inclusion. We argue that both Canada and the United States need to reconceive social inclusion in ways that address these issues and that a more capacious conception of federalism may hold the key.